2017
DOI: 10.18535/ijmsci/v4i5.11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surgical Intervention in Treatment of Tubercular Lymphadenitis in Neck Region

Abstract: INTRODUCTION -Lymphadenitis is the most common extrapulmonary manifestation of tuberculosis. It is important for otolaryngologists to be aware of TB in head and neck region and its various manifestations. Lymphadenopathy can progress to abscess and fistula formation, which can be disabling and socially unacceptable. ATT under dots is the main treatment while surgery is required for enlarged lymph nodes or tuberculous lymph node which does not regress with medication. OBJECTIVE -This study aims to find the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Sui reported 100% cure rate only after excision of all grossly enlarged lymph nodes [6]. Similarly Indulkar P et.al in their study of 91 patients of cervical tuberculosis of lymph nodes have reported a high failure rate with only 66 patients being cured by ATT alone and in the rest 25 patients who developed abscess or enlargement of lymph nodes,lymph node dissection was performed [18].…”
Section: Discussionmentioning
confidence: 95%
“…Sui reported 100% cure rate only after excision of all grossly enlarged lymph nodes [6]. Similarly Indulkar P et.al in their study of 91 patients of cervical tuberculosis of lymph nodes have reported a high failure rate with only 66 patients being cured by ATT alone and in the rest 25 patients who developed abscess or enlargement of lymph nodes,lymph node dissection was performed [18].…”
Section: Discussionmentioning
confidence: 95%
“…Among these patients, 12 (13%) recurred after the end of treatment, which suggested surgical treatment to have more promising results. 9,10 Patients with TB and diabetes had 30% greater odds of mortality, required more extended treatment, and were longer to achieve negative M.Tb cultures. Having diabetes as comorbidity negatively affects patient outcomes.…”
Section: Discussionmentioning
confidence: 99%